The Connected Community Pharmacy: Benefits for Healthcare and Implications for Health Policy - Goundrey-Smith, Stephen (Frontiers in Pharmacology, 2018)
The need for interoperability of healthcare Information Technology (IT) systems in order to provide safe, efficient, and coordinated healthcare is universally recognized. Various health economies, such as the United Kingdom, the United States, and Australia, are seeking to develop regional, state-wide, or national systems of healthcare interoperability. In England, the community pharmacy network is a significant health provider, with important implications for provision of healthcare in deprived areas because of its accessibility. Historically, however, community pharmacies have operated on a silo basis, and have not shared information on their activities with, or been able to access information from, other National Health Service (NHS) healthcare providers. The development of services such as the Electronic Prescription Service and the Summary Care Record in England have helped to connect community pharmacy with the NHS infrastructure, and more comprehensive systems and datasets are proposed to integrate community pharmacy with the NHS in future. This paper will review the benefits of the connected community pharmacy, based on developments to date and reviewing evidence from other countries. It will describe some of the future developments that will support the connected community pharmacy in England, and discuss some of the implications for pharmacists and health policy makers.